The roles of enterprise resource planning and management control on knowledge sharing - Alomari, Izzeideen A.; Amizawati Mohd Amir,; Sofiah Md Auzair,; KhairulAzman Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study signifies knowledge as strategic resources in attaining organisational mission and vision. With the increasing trend of employee turnover, the need to retain knowledge is a challenge, and thus, fostering organisational knowledge sharing is an option to uphold the knowledge. The advancement of the technology, together with management control systems have crucial roles in effectively sharing knowledge. This study aims to examine the relationship between Enterprise Resource Planning (ERP), management control (MC) and their complementarity effect towards facilitating organisational knowledge sharing (KS) practice. Questionnaires were administered to top management of randomly selected manufacturer listed in the Federation of Malaysian Manufacturers Directory. 114 usable responses were analysed using partial least square structural equation modelling (PLS-SEM). The results indicate positive and significant relationships between ERP, MC and KS, hence suggesting the knowledge sharing role of ERP and MC as governing mechanism to KS. The complementarity effect between ERP and MC was also found to be positively associated with KS. The results provide evidence on the importance of appropriate governing control mechanism in combination with enhanced technology to foster organizational knowledge-sharing practice.